2018
DOI: 10.26858/est.v1i1.7001
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of students’ higher order thinking skills (HOTS) in Wave and Optics Using IRT with Winstep Software

Abstract: This study aims to determine the Descriptions of Student Higher Order Thinking Skills (HOTS) of Singkawang STKIP physics education students. In addition, this research also aims to. This research is quantitative descriptive. Validity and reliability tests in this study will use rasch modeling with the help of Winsteps software. Through this research will be obtained the exposure of HOTS data of Singkawang STKIP physics education students on wave and optical material so that it is expected to be the basis for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 5 publications
0
7
0
4
Order By: Relevance
“…In addition to the constraints of facilities and infrastructure, learning tools are also needed that can provide facilities for students to think at a high level. The application of various learning models is useful for increasing motivation for students to think at a higher level (Kusumaningrum et al, 2019, Yang, 2015). One learning model that is able to meet these criteria is a discovery learning model that is supported by the cognitive conflict approach.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the constraints of facilities and infrastructure, learning tools are also needed that can provide facilities for students to think at a high level. The application of various learning models is useful for increasing motivation for students to think at a higher level (Kusumaningrum et al, 2019, Yang, 2015). One learning model that is able to meet these criteria is a discovery learning model that is supported by the cognitive conflict approach.…”
Section: Introductionmentioning
confidence: 99%
“…The Rasch model shows diagnostic information for improving the quality of instruments and benefits to scaling and interpretation (Willse, 2017). Some of the advantages of the Rasch model include being able to predict missing dates and data bias, measuring based on the logit scale, knowing student distribution, converting ordinal data into intervals, and showing wright maps of variables (Ölmez & Ölmez, 2019;Soeharto & Rosmaiyadi, 2018). Not only using the Rasch model for evaluation but also to determine the validity and reliability of the mathematical trauma questionnaire by using WinSteps software as well as determining the validity and reliability of the data for the Cronbach's Alpha (α) reliability evaluation (Osman et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that the level of difficulty of the items is suitable for the sample under study. It can also be observed that the correlation values are all above 0.40 and below 0.85, which reveals the inexistence of problems, as all the questions were well understood, without any misunderstandings, by the participants [ 79 ].…”
Section: Study 3 Confirmatory Studymentioning
confidence: 99%